Is the MTHFR C677T variant a genetic risk factor in the etiology of autism spectrum disorder? Is it alone or by combined with rare variants of the PHGDH gene? (Annals of Medical Research, 2022)
Aim: Autism spectrum disorder (ASD) is a group of diseases characterized by restricted interests, speech disorders, lack of reciprocal social communication. Genetic factors are predominantly responsible for the etiology of ASD. ASD genetics is complex and heterogeneous, and a variety of genetic factors has been associated with ASD. The C677T in the methylenetetrahydrofolate reductase (MTHFR) gene has been associated with the increased genetic liability for ASD in many studies. In the present study, we asked whether the MTHFR C677T variant increases the risk of ASD alone or in combination with rare harmful SNVs (MAF values are ≤ 0.001) on the phosphoglycerate dehydrogenase gene (PHGDH) in the genetic etiology of ASD.Materials and Methods: Two hundred twenty-two patients with ASD and 323 neurotypical controls were included in this study. PCR and Restriction Fragment Length Polymorphism method was used for screening the C677T. The PHGDH gene was scanned in the groups by targeted next-generation sequencing carrying C677T variant as homo-or heterozygous. Allele and genotype distributions of the C677T were analyzed by using the chi-square test. Genotype distributions were analyzed according to all four possible genetic models; homozygote (TT vs CC), heterozygote (CT vs CC), dominant (TT+CT vs CC), and recessive (TT vs CT+CC).Results: There was not any significant difference in terms of C and T allele distributions between ASD and controls (T vs C: OR = 1.16, 95% CI = 0.89-1.5, p > 0.05). There were not any significant different distributions of the 4 possible genotypes. In possible combined effects of the C677T and rare and possibly harmful SNVs of the PHGDH in the genetic etiology of ASD, we could not find any differences between patients and controls.Conclusion: No data were found to support that the MTHFR C677T variant alone or in combination with rare variants of the PHGDH gene is a genetic risk factor in the etiology of ASD.
Keywords: Autism spectrum disorder; genetic association studies; methylenetetrahydrofolate reductase; phosphoglycerate dehydrogenase